Misreading Svechin: attrition, annihilation, and historicism - Stone, David R. (My University, 2012)
Soviet military theorist Aleksandr Svechin is often misperceived as an advocate of strategies of attrition over destruction or annihilation. In fact, Svechin was an historicist, who saw the precise balance between attrition and annihilation, or defense and offense, as constantly shifting as a result of changing material circumstances. A close examination of his theoretical and historical works reveals the depth of his thinking, while his response to Russia’s 1916 Brusilov Offensive shows his support for ambitious strategies of annihilation under the proper circumstances.
Keywords: Svechin, Aleksandr Andreevich--(1878-1938); Soviet military theorists; Military history